2002
DOI: 10.1021/jo011118g
|View full text |Cite
|
Sign up to set email alerts
|

Computational Studies of Aliphatic Amine Basicity

Abstract: Computational studies have been used to examine the structural and energetic effects of adding small numbers of water molecules to ammonia, methylamine, dimethylamine, and trimethylamine, and their respective ammoniums ions using the effective fragment potential method. Distinct structural effects with only a few fragment water molecules are revealed. The complexity of structures increases with the number of water fragments with the water fragments forming complex networks. Structural and energetic effects are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 98 publications
(224 reference statements)
0
18
0
Order By: Relevance
“…The first water molecules add distinctly, while larger numbers of water molecules form hydrogen-bond networks. The thermochemistry leads toward the anomalous basicities of ammonia and alkylamines in solution …”
Section: 3 Effects Of Partial Solvation On Acidities Basicities and O...mentioning
confidence: 99%
“…The first water molecules add distinctly, while larger numbers of water molecules form hydrogen-bond networks. The thermochemistry leads toward the anomalous basicities of ammonia and alkylamines in solution …”
Section: 3 Effects Of Partial Solvation On Acidities Basicities and O...mentioning
confidence: 99%
“…To reduce this error the classical multipoles for distant (excluded) interactions can be taken into account, for example, Stone's multipole analysis (SMA) 54 or some matching rules as in other fragmentation methods can be introduced. The successful applications of effective fragment potential method, 55,56 that is, using SMA to describe interactions between classical and quantum region, to discuss different reactivity phenomena [57][58][59] indicates that incorporation of Stone's multipoles for distant interaction should improve accuracy and speed up the ELG/C calculations. The advantage of Stone's multipoles is connected with the fact that they are one-electron in nature and are computed only once in every elongation cutoff step.…”
Section: A-helix Of Polyglycinementioning
confidence: 99%
“…45 An explicit treatment of solvation effects has been used by Damrauer and coworkers to examine the basicity of aliphatic amines. 106 In this approach, up to 14 water molecules were added via the effective fragment potential method and it was found that only a few (<6) water molecules were required before significant structural and energetic effects were observed. However differences in amine basicity appear to be due to very subtle structural and solvation effects.…”
Section: Solvationmentioning
confidence: 99%